2019
DOI: 10.1155/2019/8301896
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Hand Eczema Severity and Occupational Stress: A Cross-Sectional Study

Abstract: Background Stress has been recently implicated as a contributing factor of hand eczema (HE) severity. However, published data are both rare and contradictory justifying the need of further research. The purpose of this study was to evaluate the relation between stress and HE severity. Methods This is a cross-sectional study enrolling all patients who have been attending the Dermato-allergology unit of Farhat Hached University Hospital of Sousse over a period of one year. The HE severity was assessed by the Osn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 31 publications
(44 reference statements)
3
37
0
1
Order By: Relevance
“…Although with some differences, most studies 3,15,20 Studies have shown that severity of hand eczema and frequency of eruption correlated directly with decreased quality of life. 21,22 In these studies, stress levels of patients presenting with hand eczema 10 had studied the role of stress and had noted a statistically significant association between hand eczema severity and high levels of stress. In a questionnaire-based survey, Anveden et al, 12 had studied the role of stress and it was found that hand eczema was more common among individuals who reported stress.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although with some differences, most studies 3,15,20 Studies have shown that severity of hand eczema and frequency of eruption correlated directly with decreased quality of life. 21,22 In these studies, stress levels of patients presenting with hand eczema 10 had studied the role of stress and had noted a statistically significant association between hand eczema severity and high levels of stress. In a questionnaire-based survey, Anveden et al, 12 had studied the role of stress and it was found that hand eczema was more common among individuals who reported stress.…”
Section: Resultsmentioning
confidence: 99%
“…It is known to have established and acceptable psychometric properties. 13,14,25,26 Even though PSS has been widely used in dermatology in recent years, [27][28][29][30][31] except for the study by Hafsia et al, 10 it has not been used to assess the role of stress in cases of hand eczema, and hence is underutilised. In the present study, PSS scores was calculated for all the 62 participants and it was found that 42 (67.7%) of them had increased stress scores, of which 10 (6.1%)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations